Малогабаритные высокоинформативные холестерические дисплеи с памятью - Sorokin, V. M.; Zelinskyy, R. Ya.; Rybalochka, A. V. (PE "Politekhperiodika", Book and Journal Publishers, 2008)
The development and investigation of reflective displays operating on electro‑optical bistability effects in cholesteric liquid crystals (LCs) are considered. Using dynamic hysteresis as the main characteristic of bistable high‑informative cholesteric displays, a number of methods for electronic control of matrix screens are proposed. The advantages of this class of LC devices are demonstrated in comparison with reflective displays based on other electro‑optical effects in liquid crystals. Further directions for improving bistable cholesteric displays with memory are discussed.